A peppermint oil emulsion stabilized by resveratrol-zein-pectin complex particles: Enhancing the chemical stability and antimicrobial activity in combination with the synergistic effect. (June 2020) - Cheng, Hao; Khan, Muhammad Aslam; Xie, Zhenfeng; Tao, Shengnan; Li, Yunxing; Liang, Li
Abstract: The combination of different antimicrobial agents might produce synergistic effects and has gained increasing interest. Interfacial engineering of emulsion systems has been developed to co-encapsulate and protect bioactive components with different solubility. In this study, peppermint oil and resveratrol display synergistic effect against the Gram-positive bacteria Staphylococcus aureus and the Gram-negative bacteria Salmonella Typhimurium . Partially wettable resveratrol-loaded zein-pectin complex particles with a three-phase contact angle of ~78° were fabricated via a desolvation method. Peppermint oil emulsions with the co-inclusion of resveratrol were successfully prepared by zein-pectin complex particles, showing a high encapsulation efficiency for peppermint oil (~88%) and resveratrol (~99%). Addition of pectin decreased size distribution of the emulsions, improved antimicrobial activity, physical and chemical stability and prolonged antimicrobial efficiency against Staphylococcus aureus and Salmonella Typhimurium . Overall, the current study may have a valuable contribution to develop an efficient antimicrobial system based on the synergistic effect of combined agents and a single emulsion stabilized by protein-polysaccharide complex particles. Graphical abstract: Image 1 Highlights: Resveratrol was loaded in zein-pectin particles with partial wettability. Peppermint oil and resveratrol were co-encapsulated in zein-pectin O/W emulsions. Mixture of particles and pectin at the interface decreased size of emulsions. Peppermint oil and resveratrol display synergistic antimicrobial activity. Addition of pectin improved antimicrobial and physicochemical stability.